Developing a System for Notification of Forgetting to Close the Dormitory Door with Mobile Application using Internet of Things - Phiphatkamtorn, Phanthawat; Naowarat, Jenjira; Khruahong, Sanya (Journal of Applied Informatics and Technology, 2023)
Dormitories are very popular with the Thai people. From the research questionnaire of Thammasat University, it was found that people decide to rent accommodation in each place. They will consider the residence's safety as the second priority after the location that is convenient travel. Therefore, the safety factor of the shelter is the top factor that tenants will consider when choosing a dormitory. The crime may cause damage to property, mental state, and possibly death of the tenant. Moreover, one problem is the dormitory without a security guard or leaving the door open. Therefore, the researcher recognizes the importance of the above problem. Therefore, we use the Internet of Things to help the dormitory operators and dormitory tenants. It has a working process of communication or transmitting data between devices. It has a distinctive feature that is to increase comfort, quickly and accurately. The objectives of this research are as follows: 1) to develop a notification system. In the case of forgetting to close the dormitory door with the application of the Internet of Things 2) to evaluate the system development with the sample group being dormitory tenants and dormitory owners, 20 people. For research to achieve such objectives. We have developed a system for checking if forgetting to close the dormitory door. The system will send a notification to the chat group of the dormitory tenants or private chat of the dorm owner and a sound notification from the device when it forgets to close the dormitory door after it has been used for 30 seconds. The system has two important devices used to develop the system are 1) microcontroller board and 2) ultrasonic sensor. In the experiment, we left the door open forty times. The results showed that a notification was sent to a chat group of dormitory tenants and dormitory owners. There were audible notifications from the device, 2.854 seconds for the average time the notification was sent to the chat. The average time it took the device to process it before sending the sound was 2.681 seconds. In addition, the evaluation of the system's satisfaction by 20 tenants found that the results were a good level.